Comparison of mandibular first molar mesial root canal morphology using micro-computed tomography and clearing technique. (August 2014) - Kim, Yeun; Perinpanayagam, Hiran; Lee, Jong-Ki; Yoo, Yeon-Jee; Oh, Soram; Gu, Yu; Lee, Seung-Pyo; Chang, Seok Woo; Lee, Woocheol; Baek, Seung-Ho; Zhu, Qiang; Kum, Kee-Yeon
Abstract: Objective. Micro-computed tomography (MCT) with alternative image reformatting techniques shows complex and detailed root canal anatomy. This study compared two-dimensional (2D) and 3D MCT image reformatting with standard tooth clearing for studying mandibular first molar mesial root canal morphology. Materials and methods. Extracted human mandibular first molar mesial roots ( n = 31) were scanned by MCT (Skyscan 1172). 2D thin-slab minimum intensity projection (TS-MinIP) and 3D volume rendered images were constructed. The same teeth were then processed by clearing and staining. For each root, images obtained from clearing, 2D, 3D and combined 2D and 3D techniques were examined independently by four endodontists and categorized according to Vertucci's classification. Fine anatomical structures such as accessory canals, intercanal communications and loops were also identified. Results. Agreement among the four techniques for Vertucci's classification was 45.2% (14/31). The most frequent were Vertucci's type IV and then type II, although many had complex configurations that were non-classifiable. Generally, complex canal systems were more clearly visible in MCT images than with standard clearing and staining. Fine anatomical structures such as intercanal communications, accessory canals and loops were mostly detected with a combination of 2D TS-MinIP and 3D volume-rendering MCT images. Conclusions. Canal configurations and fine anatomic structures were more clearly observed in the combined 2D and 3D MCT images than the clearing technique. The frequency of non-classifiable configurations demonstrated the complexity of mandibular first molar mesial root canal anatomy.